2015
DOI: 10.1007/s11655-015-2175-5
|View full text |Cite
|
Sign up to set email alerts
|

Dalitong Granule (达立通颗粒) combined with electroacupuncture in the treatment of functional dyspepsia: A randomized controlled trial

Abstract: Combined treatment of DG and EA could increase both plasma motilin and electrogastrographic frequencies, promote gastric emptying, alleviate the symptom of dyspepsia so as to increase quality of life, with better safety and long-term effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 11 publications
0
49
0
1
Order By: Relevance
“…Previously, most herbal trials were performed with open-labeled methods. [ 20 21 22 23 ] In the present study, we designed the placebo, which contained 5% of the active ingredient of the medicine, to have a similar taste, appearance, and smell without having a pharmacologically active effect. In the recruitment period, the patients who positively reacted to the placebo were excluded, which could effectively avoid the placebo effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, most herbal trials were performed with open-labeled methods. [ 20 21 22 23 ] In the present study, we designed the placebo, which contained 5% of the active ingredient of the medicine, to have a similar taste, appearance, and smell without having a pharmacologically active effect. In the recruitment period, the patients who positively reacted to the placebo were excluded, which could effectively avoid the placebo effect.…”
Section: Discussionmentioning
confidence: 99%
“…All articles included in the analysis were designed as randomized clinical trial studies. Five studies [ 12 15 , 17 ] used random number tables or lists, while the others did not detail the specific methods of randomization. An attempt to contact the authors to clarify the method did not generate any responses.…”
Section: Resultsmentioning
confidence: 99%
“…There was 3 sham intervention (sham-EA) [ 12 , 13 , 16 ] in the included studies and participant blinding was deemed to be applicable. Three trials [ 13 15 ] reported dropout rates of patients. All trials reported all outcome measurements mentioned in the methods and were therefore deemed to be at low risk of attrition bias.…”
Section: Resultsmentioning
confidence: 99%
“…Fang et al [88] found that acupuncture relieved gastrointestinal symptoms and signs using resting-state fMRI, which may be due to the normalization of brain-gut axis in FD patients. (3) Molecular mechanism: A study performed by Zhang and Guo showed that EA increased plasma motilin, thereby promoting gastric emptying and alleviating the symptom of dyspepsia [89]. (4) Metabolomics mechanisms: Li et al [90] found that stimulation of different acupoints regulates the plasma levels of markers of FD as revealed by high performance liquid chromatography-mass spectrometry combined with metabolomics.…”
Section: Discussionmentioning
confidence: 99%